Is the Risk of Diabetes Lower in Patients With Atrial Fibrillation Treated With Direct Oral Anticoagulant Compared to Warfarin? - Liu, Xuyang; Feng, Shenghui; Chen, Zhuohui; Zhou, Yue; Yin, Kang; Xue, Zhengbiao; Zhu, Wengen (Frontiers in Cardiovascular Medicine, 2022)
Background: The use of anticoagulants is an established strategy to prevent stroke, embolism, and cardiovascular mortality in patients with atrial fibrillation (AF), but its role in the prevention of incident diabetes is unclear. We aimed to investigate this question by using participant data from cohort studies. Methods: We conducted a meta-analysis of participants to investigate the impact of direct oral anticoagulants (DOACs) on the risk of new-onset diabetes in AF patients. The collection of related data was performed in the PubMed and EMBASE databases until December 2021, including studies associated with evaluating the correlation between DOACs and incident diabetes. The hazard ratios (HRs) and 95% confidence intervals (CIs) were adjusted by the random-effects model with an inverse variance method. Results: Two cohort studies with a total of 24,434 patients were included in this study (warfarin: n=6906; DOACs: n=17528). Compared with warfarin, the use of DOACs could reduce the incident diabetic risk in AF patients (HR=0.75, 95%CI, 0.68-0.82). Investigations about the effects of three major classes of DOACs showed that the individual use of dabigatran (HR=0.76, 95%CI: 0.64-0.90), rivaroxaban (HR=0.74, 95%CI: 0.64-0.87), apixaban (HR=0.74, 95%CI: 0.60-0.92) and the combined use of rivaroxaban and apixaban (HR=0.74, 95%CI: 0.66-0.84) could reduce the risk of new-onset diabetes compared with warfarin. This risk reduction effect could be observed in both male and female groups (HR=0.73, 95%CI: 0.64-0.84, P<0.00001; HR=0.82, 95%CI, 0.82-0.99, P=0.04). Conclusions: Treatment with DOACs compared with warfarin reduced the risk of new-onset diabetes in both male and female patients with AF.